Effects of environmental conditions, core temperature, and hydration status on women`s soccer performance - Collins, S. M.; Poague, A.; Huggins, R.; Bowman, T. G. (International Journal of Strength and Conditioning, 2025)
National Collegiate Athletics Association (NCAA) Division III athletes have restrictive rules on preseason practice timelines leading to questions about how performances are affected by environmental conditions during preseason practices.